Software-Qualität - überall! - Excel-lente Software - Bals, Jan-Christopher; Christ, Fabian; Engels, Gregor; Sauer, Stefan (Forschungsforum Paderborn)

A Model-Driven Approach to Discovery, Testing and Monitoring of Web Services - Lohmann, Marc; Mariani, Leonardo; Heckel, Reiko (Test and Analysis of Web Services)
Service-oriented computing is distinguished by its use of dynamic discovery and binding for the integration of services at runtime. This poses a challenge for testing, in particular, of the interaction between services. We propose a model-driven solution to address this challenge. Service descriptions are promoted from largely syntactical to behavioural specifications of services in terms of contracts (pre-conditions and effects of operations), expressed in a visual UML-like notion. Through mappings to semantic web languages and the Java Modeling Language (JML) contracts support the automatic discovery of services as well as the derivation of test cases and their execution and monitoring. We discuss an extended life cycle model for services based on the model-driven approach and illustrate its application using a model of a hotel reservation service.

Architectural Style-based Modeling and Simulation of Middleware for Mobile Systems - Guo, Ping
Today, mobility is one of the most important market and technology trend within information and communication technology. As the demand for rapid deployment of dependable mobile applications increases, middleware for mobile systems is emerging as one of the most active areas of system research in mobility. The middleware is a set of distributed software services that exists between distributed operating systems and mobile applications. The key to the middleware is to provide support across the mobile application domains, help application developers overcome the complexity and problems brought by mobility, and enhance dependability and usability of developed mobile applications. The criticality and pervasiveness of middleware for mobile systems is continually growing. However, the design and development of the middleware are difficult tasks, and it is not easy to ensure the quality of a developed middleware. This is mainly caused by the increasing complexity of the middleware. In addition, the great diversity of this area makes it very difficult for the designers to reuse the already established design knowledge or successful experience when building new systems. All these make the design process quite inefficient and unpredictable, and therefore risking the project. “One man’s magic is another man’s engineering”. Engineering design is much more routine than innovative. Founding on this fundamental notion in software engineering, we develop an architectural style-based approach to deal with the problems in the thesis. We build architectural styles for a class of related middleware. The style represents a common form of design, which originates from the results that practitioners have achieved in one area. The style is formulated to repeat successes and avoid failures from previous projects. When building a new middleware, the designers and developers do not need to explore all possible alternatives for its supported architecture. Instead, they can use the architectural style that is effective for the middleware. They can define the design as instances of the style, or they can use the style as a reference model for further improvement and development. By structuring the design space for a family of related middleware, the style can drastically simplify the process of building a middleware, reduce costs of implementation through reusable infrastructure, and improve system integrity through style-specific analysis and checks. We develop the approach based on UML-like meta modeling and graph transformation techniques to support sound methodological principles, powerful modeling, formal analysis and refinement. The approach consists of several main parts: the modeling language that supports specification of the style and mobility, the refinement formalization that ensures that an abstract style is correctly refined to a concrete one, as well as the consistency check framework that validates behavioral consistency between two styles on different abstract layers. With the Fujaba simulation tool support, we also develop a style-based engineering process that helps us to efficiently develop correct and consistent styles. Besides, it allows a seamless integration of our approach into the well-known object oriented design. By providing a concrete example of how to construct the style for a class of related middleware, and how to use the style to help the design and development of a new middleware, we show that the architectural style-based approach is useful and practical.

Constructing an Emblematic Northern Space. The New Brighton Photographs of Martin Parr and Tom Wood - Tönnies, Merle (Spatial Practices 2)

Quantum dots as tunable scatterers for 2D- and 1D-electron systems - Marquardt, Bastian; Russ, Marco; Lorke, Axel; Meier, Cedrik; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

Silicon nanoparticles: Absorption, emission, and the nature of the electronic bandgap - Meier, Cedrik; Gondorf, Andreas; Lüttjohann, Stephan; Lorke, Axel; Wiggers, Hartmut (Journal of Applied Physics)

Technique for tilting GaAs photonic crystal nanocavities out of plane - Meier, Cedrik; Hennessy, Kevin (Applied Physics Letters)

Temperature-induced crossover between bright and dark exciton emission in silicon nanoparticles - Lüttjohann, S; Meier, Cedrik; Offer, M; Lorke, A; Wiggers, H (Europhysics Letters (EPL))

Effect of User Mobility in Coded Cooperative Systems with Joint Partner and Cooperation Level Selection - Valentin, Stefan; Karl, Holger (IEEE Wireless Communications and Networking Conference, WCNC 2007, Hong Kong, China, 11-15 March, 2007)

Multi-rate Relaying for Performance Improvement in IEEE 802.11 WLANs - Marie Feeney, Laura; Cetin, Bilge; Hollos, Daniel; Kubisch, Martin; Mengesha, Seble; Karl, Holger (Wired/Wireless Internet Communications, 5th International Conference, WWIC 2007, Coimbra, Portugal, May 23-25, 2007, Proceedings)

Analysis of Model Transformations via Alloy - Anastasakis, Kyriakos; Bordbar, Behzad; Küster, Jochen (Proceedings of the workshop on Model-Driven Engineering, Verification and Validation (MoDeVVA 2007), Nashville, TN (USA))

Towards Model-Driven Unit Testing - Engels, Gregor; Güldali, Baris; Lohmann, Marc (Proceedings of the 2006 International Conference on Models in Software Engineering (MoDELS 2006))
The Model-Driven Architecture (MDA) approach for constructing software systems advocates a stepwise refinement and transformation process starting from high-level models to concrete program code. In contrast to numerous research efforts that try to generate executable function code from models, we propose a novel approach termed model-driven monitoring. On the model level the behavior of an operation is specified with a pair of UML composite structure diagrams (visual contract), a visual notation for pre- and post-conditions. The specified behavior is implemented by a programmer manually. An automatic translation from our visual contracts to JML assertions allows for monitoring the hand-coded programs during their execution. In this paper we present an approach to extend our model-driven monitoring approach to allow for model-driven unit testing. In this approach we utilize the generated JML assertions as test oracles. Further, we present an idea how to generate sufficient test cases from our visual contracts with the help of model-checking techniques.

Analysis of UML Activities with Dynamic Meta Modeling Techniques - Soltenborn, Christian; Engels, Gregor (Symposium "A Formal Semantics for UML" (satellite event of the MoDELS conference 2006), Genova (Italy))

Consistency of Business Process Models and Object Life Cycles - Ryndina, Ksenia; Küster, Jochen; Gall, Harald (Models in Software Engineering (1st Workshop on Quality in Modeling at MoDELS 2006, Genoa (Italy)))

On the Pitfalls of UML Activity Modeling - Schattkowsky, Tim; Förster, Alexander (Proceedings of the ICSE workshop on Modeling in Software Engineering (MISE 2007), Minneapolis, MN (USA))
With the introduction of new Petri net-like semantics for Activities in UML 2.0, these have become a complete language for modeling behavior. Thus, UML Activities are nowadays investigated for application in many areas from embedded systems to business process modeling. However, some issues have been discovered that currently seem to limit the practical applicability of Activities. In this paper, we present an overview of the identified semantic and syntactic problems, and point at possible solutions and directions for future research.

Strong spin–orbit interactions in carbon doped p-type GaAs heterostructures - Grbić, B.; Leturcq, R.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Aharonov–Bohm oscillations in p-type GaAs quantum rings - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

High sensitivity far-infrared detection by resonant inter-Landau-level scattering - Notthoff, C.; Lorke, A.; Reuter, Dirk (Physica E: Low-dimensional Systems and Nanostructures)

Aharonov–Bohm effect of quantum Hall edge channels - Giesbers, A.J.M.; Zeitler, U.; Reuter, Dirk; Wieck, A.D.; Biasiol, G.; Sorba, L.; Maan, J.C. (Physica E: Low-dimensional Systems and Nanostructures)

Magnetic-field-induced modification of the wave-functions in InAs quantum dots - Lei, W.; Wibbelhoff, O.; Notthoff, C.; Marquardt, B.; Reuter, Dirk; Wieck, A.D.; Lorke, A. (Physica E: Low-dimensional Systems and Nanostructures)

Influence of In0.15Ga0.85As capping layers on the electron and hole energy levels of InAs quantum dots - Richter, Mirja; Reuter, Dirk; Duboz, Jean-Yves; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

Capacitance–voltage spectroscopy of post-growth annealed InAs quantum dots - Reuter, Dirk; Roescu, Razvan; Mehta, Minisha; Richter, Mirja; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Site-selective growth of self-assembled InAs quantum dots on focused ion beam patterned GaAs - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A.D.; Remhof, A. (Physica E: Low-dimensional Systems and Nanostructures)

Quantum dots as tunable scatterers for 2D- and 1D-electron systems - Marquardt, Bastian; Russ, Marco; Lorke, Axel; Meier, Cedrik; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

A comparison: 2D electron- and hole systems in the fractional quantum Hall regime - Hadzibrahimovic, Adriana; Dethlefsen, Annelene F.; Reuter, Dirk; Wieck, Andreas D.; Tranitz, Hans-Peter; Wegscheider, Werner; Haug, Rolf J. (Physica E: Low-dimensional Systems and Nanostructures)

Hot-electron bend resistance in a ballistic GaAs/AlGaAs cross junction - Wiemann, M.; Cetinkaya, A.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magneto-ballistic effects in non-centrosymmetric GaAs/AlGaAs cross junctions - Wieser, U.; Knop, M.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magneto-optical probing of weak disorder in a two-dimensional hole gas - Bryja, Leszek; Wójs, Arkadiusz; Misiewicz, Jan; Potemski, Marek; Reuter, Dirk; Wieck, Andreas (Physical Review B)

Spin-controlled LEDs and VCSELs - Hövel, S.; Gerhardt, N. C.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W. (physica status solidi (a))

Subsecond Spin Relaxation Times in Quantum Dots at Zero Applied Magnetic Field Due to a Strong Electron-Nuclear Interaction - Oulton, R.; Greilich, A.; Verbin, S. Yu.; Cherbunin, R. V.; Auer, T.; Yakovlev, D. R.; Bayer, M.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Sequential and cotunneling behavior in the temperature-dependent thermopower of few-electron quantum dots - Scheibner, R.; Novik, E. G.; Borzenko, T.; König, M.; Reuter, Dirk; Wieck, A. D.; Buhmann, H.; Molenkamp, L. W. (Physical Review B)

Exciton fine structure inInGaAs∕GaAsquantum dots revisited by pump-probe Faraday rotation - Yugova, I. A.; Greilich, A.; Zhukov, E. A.; Yakovlev, D. R.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Robust manipulation of electron spin coherence in an ensemble of singly charged quantum dots - Greilich, A.; Wiemann, M.; Hernandez, F. G. G.; Yakovlev, D. R.; Yugova, I. A.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Universal behavior of the electrongfactor inGaAs∕AlxGa1−xAsquantum wells - Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Kiselev, A. A.; Bayer, M.; Petrov, V. V.; Dolgikh, Yu. K.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Charge and spin dynamics in a two-dimensional electron gas - Pugžlys, A; Rizo, P J; Ivanin, K; Slachter, A; Reuter, Dirk; Wieck, A D; Wal, C H van der; Loosdrecht, P H M van (Journal of Physics: Condensed Matter)

Magnetic and structural properties of Gd-implanted zinc-blende GaN - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Wieck, A. D.; Ney, V.; Kammermeier, T.; Ney, A.; Schörmann, J.; Potthast, S.; As, D. J.; Lischka, K. (Applied Physics Letters)

Experimental imaging and atomistic modeling of electron and hole quasiparticle wave functions inInAs∕GaAsquantum dots - Bester, G.; Reuter, Dirk; He, Lixin; Zunger, A.; Kailuweit, P.; Wieck, A. D.; Zeitler, U.; Maan, J. C.; Wibbelhoff, O.; Lorke, A. (Physical Review B)

Focused ion beam implantation induced site-selective growth of InAs quantum dots - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A. D.; Remhof, A. (Applied Physics Letters)

Nuclei-Induced Frequency Focusing of Electron Spin Coherence - Greilich, A.; Shabaev, A.; Yakovlev, D. R.; Efros, Al. L.; Yugova, I. A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Science)

Measurement of the specific heat of a fractional quantum Hall system - Schulze-Wischeler, F.; Zeitler, U.; v. Zobeltitz, C.; Hohls, F.; Reuter, Dirk; Wieck, A. D.; Frahm, H.; Haug, R. J. (Physical Review B)

Systematic study of carrier correlations in the electron-hole recombination dynamics of quantum dots - Berstermann, T.; Auer, T.; Kurtze, H.; Schwab, M.; Yakovlev, D. R.; Bayer, M.; Wiersig, J.; Gies, C.; Jahnke, F.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

The Influence of Device Geometry on Many-Body Effects in Quantum Point Contacts: Signatures of the 0.7 Anomaly, Exchange and Kondo - Koop, E. J.; Lerescu, A. I.; Liu, J.; van Wees, B. J.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Journal of Superconductivity and Novel Magnetism)

CYCLOTRON RESONANCE IN COUPLED BILAYERS IN HIGH MAGNETIC FIELDS - GÜRTLER, A.; ZEITLER, U.; MAAN, J. C.; Reuter, Dirk; WIECK, A. D. (International Journal of Modern Physics B)

Aharonov-Bohm Oscillations in the Presence of Strong Spin-Orbit Interactions - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physical Review Letters)

Spin Coherence of Holes inGaAs/(Al,Ga)AsQuantum Wells - Syperek, M.; Yakovlev, D. R.; Greilich, A.; Misiewicz, J.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Evidence for the Luttigger liquid density of states in transport across the incompressible stripe at fractional filling factors - Deviatov, E. V; Kapustin, A. A; Dolgopolov, V. T; Lorke, A; Reuter, Dirk; Wieck, A. D (Europhysics Letters (EPL))

Hole levels in InAs self-assembled quantum dots - Blokland, J. H.; Wijnen, F. J. P.; Christianen, P. C. M.; Zeitler, U.; Maan, J. C.; Kailuweit, P.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Bildungsstandards in der Berufsbildung – Kompetenzen messen auf Basis des Rasch-Modells. Konzeption und Erprobung der Messung - Beutner, Marc (Paderborner Forschungs- und Entwicklungswerkstatt)

Die Förderung interkulturellen Verständnis in der beruflichen Bildung - Beutner, Marc (Fremde Kulturen verstehen – fremde Kulturen lehren. Theorie und Praxis der Vermittlung interkultureller Kompetenz)

Stierstorfer, K. / L. Volkmann (Hg.): Kulturwissenschaft Interdisziplinär - Tönnies, Merle (Anglistik. International Journal of English Studies)